2021
DOI: 10.2147/jep.s296767
|View full text |Cite
|
Sign up to set email alerts
|

Application of Topical Sucralfate and Topical Platelet-Rich Plasma Improves Wound Healing in Diabetic Ulcer Rats Wound Model

Abstract: Purpose One of the most serious and devastating complications of diabetes mellitus is diabetic ulcers. They are difficult to treat and often result in limb loss. Topical sucralfate and platelet-rich plasma have the potential to improve the healing outcomes of chronic ulcers, including diabetic ulcers. This research aims to determine the effectiveness of sucralfate and platelet-rich plasma therapy for the improvement of diabetic ulcer wound healing. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Thus, in our study, there was no statistical difference in the healing rates of diabetic foot ulcer with and without adding sucralfate to topical mupirocin ointment. This is in contrast with some studies, which have observed better healing rates of DFUs following the addition of sucralfate [17][18][19][20]. However, our study is consistent with the study by Ala et al, which did not observe any improvement in the healing rates of chronic ulcers after the addition of sucralfate [21].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, in our study, there was no statistical difference in the healing rates of diabetic foot ulcer with and without adding sucralfate to topical mupirocin ointment. This is in contrast with some studies, which have observed better healing rates of DFUs following the addition of sucralfate [17][18][19][20]. However, our study is consistent with the study by Ala et al, which did not observe any improvement in the healing rates of chronic ulcers after the addition of sucralfate [21].…”
Section: Discussionsupporting
confidence: 86%
“…The wound protection and repair mechanism of sucralfate appears to be related to its ability to maintain blood vessel integrity. As one of the main pathological mechanisms of diabetes mellitus is vasculopathy, sucralfate would help in maintaining adequate blood flow, thus improving the bioavailability of wound healing growth factors [12]. The results of this research also seem to follow the clinical evidence noted by Nagalakshmi, Amalan and Anandan [13] regarding the topical use of sucralfate in the healing of epithelial wounds.…”
Section: Santos and Raosupporting
confidence: 77%
“…41 It is a cytoprotective agent used to prevent and treat various diseases such F I G U R E 3 EGF immunohistochemistry staining of groups at days 7, 14 and 21 as gastrointestinal diseases, reflux, gastritis and peptic ulcer. 42,43 At low pH conditions, sucralfate produces a polyanionic gel that binds proteins in the ulcer crater, which binds many growth factors, protecting them from proteolytic degradation 44 and increasing their availability. 45 Previous studies have proven that sucralfate interacts with several growth factors to promote epithelial wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Sucralfate is the aluminium hydroxide salt of the disaccharide sucrose octasulphate 41 . It is a cytoprotective agent used to prevent and treat various diseases such as gastrointestinal diseases, reflux, gastritis and peptic ulcer 42,43 . At low pH conditions, sucralfate produces a polyanionic gel that binds proteins in the ulcer crater, which binds many growth factors, protecting them from proteolytic degradation 44 and increasing their availability 45 .…”
Section: Discussionmentioning
confidence: 99%